AN EXPLORATORY ASSESSMENT OF THE SUSTAINABILITY PERFORMANCE OF THE CONSTRUCTION INDUSTRY - Ray, Amitava; Ghosh, Sudipta; Mandal, Madhab Candra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
This research aims to evaluate the sustainability performance of six India-based construction organizations by considering the triple bottom line approach to sustainability (environmental, social, and economic). First, the significant parameters for evaluating performance are identified from an extensive literature review. Second, data are collected by developing a questionnaire and carrying out a survey with selected industry experts. Subsequently, an integrated framework is developed in which item analysis examines the consistency of the data, principal component analysis determines the criteria weights, and a simple additive weighting method ranks organizations according to their performance scores. Finally, the benchmark organization is identified and its strategy has been explored. Additionally, the critical parameters in each stage of the construction supply chain are identified using the weighted mean method. The results reveal that ‘Capital Budgeting’, ‘Lifecycle Design’, ‘Use of Energy-Efficient Technology’, and ‘Cost of Waste Disposal’ are the most influential parameters in the inception, design and planning, construction and maintenance, and demolition and reverse logistics stages, respectively.